2016
DOI: 10.5430/css.v2n2p44
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic transhiatal repair of esophageal rupture in Boerhaave Syndrome is a safe and effective treatment

Abstract: Boerhaave Syndrome, also known as spontaneous esophageal rupture, is a rare condition with an estimated mortality of 20%-40%. Conventional surgical repair with the intention of primary repair remains the mainstay of treatment in esophageal rupture in Boerhaave syndrome. We present our experience with 2 cases that underwent laparoscopic transhiatal repair of esophageal rupture in Boerhaave Syndrome. Both cases presented with left chest and abdominal pain after vomiting, and were normotensive on admission. In bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Two patients followed a good postoperative course, but 1 patient subsequently succumbed to multi-organ failure. Since then, Kimberley et al [ 6 ], Yeo et al [ 7 ], Hayakawa et al [ 8 ], and Aiolfi et al [ 9 ] have reported a total of 5 cases of Boerhaave's syndrome repaired by only laparoscopic surgery via the transhiatal route. There were no reports of mortality, and good postoperative results were obtained, except for the early case of Landen and El Nakadi [ 5 ] (Table 1 ) [ 6 , 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two patients followed a good postoperative course, but 1 patient subsequently succumbed to multi-organ failure. Since then, Kimberley et al [ 6 ], Yeo et al [ 7 ], Hayakawa et al [ 8 ], and Aiolfi et al [ 9 ] have reported a total of 5 cases of Boerhaave's syndrome repaired by only laparoscopic surgery via the transhiatal route. There were no reports of mortality, and good postoperative results were obtained, except for the early case of Landen and El Nakadi [ 5 ] (Table 1 ) [ 6 , 7 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, Kimberley et al [ 6 ], Yeo et al [ 7 ], Hayakawa et al [ 8 ], and Aiolfi et al [ 9 ] have reported a total of 5 cases of Boerhaave's syndrome repaired by only laparoscopic surgery via the transhiatal route. There were no reports of mortality, and good postoperative results were obtained, except for the early case of Landen and El Nakadi [ 5 ] (Table 1 ) [ 6 , 7 , 8 , 9 ]. When performing the laparoscopic esophageal repair via the transhiatal route, avoiding penetrating the pleura is vital as it is important not to spread the inflammation in the thoracic cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The mainstay of treatment is pleural and mediastinal debridement combined with esophageal repair and spillage prevention (24). Esophageal wall closure may be achieved via primary suture with patch reinforcement or over a T-tube drainage to create a controlled esophagocutaneous fistula (12)(13)(14)(15)(16)(17). Major resection with or without primary reconstruction has been described but is matter of debate especially in defeated and septic patients (4).…”
Section: Discussionmentioning
confidence: 99%